PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOSIAL RESPONSIBILITY TERHADAP TINDAKAN PAJAK AGRESIF (Studi Empiris Perusahaan Manufaktur yang listing di BEI Tahun 2012-2015) - Mohammad Zainul Abidin; Noor Shodiq Askandar; Afifudin Afifudin (Universitas Islam Malang, 2018)
ABSTRACTThis study was conducted with the aimof : to knowthe adherents ofgoodcorporategovemance and corporatesocialresponsibiliti against taxaggressiveaction.The population used in this study are all manufacturing companies listed onIndonesia Stock Exchange BED in 2012-2015. The sample selection usingpurposte sampling. Based on criteria. Diperolch RS perfection that m samples inthis study.The method used in Based on the results of the analysis put forward someconclusions as follows: F test results show that the variable level of adherentsgood governance and social simultaneously have no effect on aggressive taxaction. 2) The result of t test shows that for the influence of good corporategovenance and responsibiliti partially do not have adherence to aggressive taxaction.Keywords: good corporate govenance, corporate social responsibilio, taxaggressive